(469) تخطيط القوي العاملة علي المستوي القومي(الجزء الاول) Workforce planning at the national level (Part 1) - محمد ناظم محمد حنفي (معهد التخطيط القومي, 2026)
تتناول هذه المذكرة في الجزء الاول الأطر النظرية والتطبيقية لـ "تخطيط القوى العاملة على المستوى القومي"، معتبرة إياه جزءاً لا يتجزأ من نظام التخطيط الشامل للدولة، يستعرض البحث مفهوم "ميزان القوى العاملة" كأداة لتصوير الموارد البشرية المتاحة وتوزيعها على القطاعات الإنتاجية والخدمية، مع التركيز على "سياسة الحد الأقصى للعمالة" كاستراتيجية اتبعتها بعض الدول الاشتراكية (مثل بولندا) في مراحل تصنيعها الأولى لتحقيق التشغيل الكامل وزيادة معدلات التراكم الرأسمالي من خلال الاستغلال الأقصى للطاقات الإنتاجية وعدد الورديات.كما يحلل الملف الإشكاليات الاقتصادية الناتجة عن هذه السياسة، مثل التناقض المحتمل بين نمو العمالة وانخفاض إنتاجية العامل أو الأجور الحقيقية في الأجل القصير. ويقدم البحث بدائل ومقترحات للمفاضلة بين زيادة الاستهلاك وزيادة الاستثمار، مستخدماً نماذج رياضية لتقدير "فترة الانتقال" اللازمة لتحقيق التوازن الاقتصادي، ويخلص البحث إلى أن نجاح تخطيط القوى العاملة يتطلب مرونة في التعامل مع المتغيرات التكنولوجية والتنظيمية، لضمان تحويل الفائض البشري إلى قوة منتجة تدعم الدخل القومي وترفع مستويات المعيشة على المدى الطويل. This paper examines the theoretical and practical frameworks of "national workforce planning," considering it an integral part of the state's comprehensive planning system. The research explores the concept of "labor force balance" as a tool for mapping available human resources and their distribution across productive and service sectors. It focuses on "maximum employment policy," a strategy adopted by some socialist countries (such as Poland) during their early industrialization phases to achieve full employment and increase capital accumulation rates through the maximum utilization of productive capacities and shifts. The paper also analyzes the economic problems arising from this policy, such as the potential contradiction between labor growth and a decline in worker productivity or real wages in the short term. It presents alternatives and proposals for balancing increased consumption with increased investment, using mathematical models to estimate the "transition period" necessary to achieve economic equilibrium. The research concludes that successful workforce planning requires flexibility in adapting to technological and organizational changes to ensure the transformation of surplus labor into a productive force that supports national income and raises living standards in the long term.